Thomas Merton: Mystic Teacher for Our Age - Finley, James S. (The Merton annual, 2015)
In this article, the author focuses on spiritual directions given by American writer Thomas Merton in his writings. Topics discussed include risk of angelism when one forget his identity as a human and try to act as angelic; concept of death that everybody has to die alone no matters how many people are with a person; and meeting of Merton with Japanese author D. T. Suzuki in 1964 at Columbia University.